Dental Health Staus of Rural Population in District Matiari - Maham Shah, Muneer Ahmed Banglard, Huma Shah, Khushboo Yousfani (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective; Health negligence is common in our society, so objective is to develop awareness among families of rural population of Matiari about periodontal diseases and overall health. Study Design: Observational, descriptive study. Place & Duration: Study was conducted in medical and dental camp at SDS farms Matiari on June 20’’’ and 21" 2015. Material & Methods: A total of 350 patients were examined clinically for periodontal diseases who visited free dental and medical camp. Results: Male remained dominant victim of the disease (51.4%) females (40.6%), Males 5.7% and females 2.3% were free from disease from subjects selected. According to age group patient’s prevalence rate ofperiodontitis was high in 31 to 60 years age. Conclusion: Periodontitis is a chronic inflammatory and non communicable disease that will lead to tooth loss. Attention should be given to the rural areas of Sindh as negligence may lead to periodontitis and other infections and ultimately there will be tooth loss.